Sistem Kontrol dan Monitoring Suhu Air Kolam Ikan Lele Fardu Farm Menggunakan PLC Outseal Mega V.3 dengan Sensor BGT-D718-PH Berbasis IoT - Irvan, Mhd Abdinul; Zarory, Hilman; Ullah, Aulia; Faizal, Ahmad (Forum Kerjasama Pendidikan Tinggi, 2024)
In cultivating catfish, there are several things that must be considered, namely the water temperature of the catfish pond. High temperatures have a stressful impact on fish, if low temperatures inhibit fish growth. Currently, most catfish farmers check the water temperature manually, by going to the pond to check with a manual measuring instrument, this has shortcomings in terms of accuracy and is time consuming. To overcome this problem, this research discusses controlling and monitoring the temperature of catfish ponds using the Outseal Mega V.3 PLC and Internet of Things (IoT) based BGT-D718-PH Sensor. With Outseal Mega V.3 PLC control which regulates the on and off logic status of devices connected to the PLC, one of which is the Bgt-D718-Ph temperature sensor. This sensor is used as an input to read the pool temperature value which replaces manual measuring instruments, so the system checks the pool water temperature automatically. Then the temperature sensor data is collected and displayed on the Blynk application in real time using Esp8266 via the internet network. The main aim of this research is to increase efficiency in raising catfish by controlling and monitoring the water temperature of catfish ponds. Through the integration of IoT and PLC technology, the system can monitor water temperature in real-time, control the temperature of the pond water with upper and lower limits if the temperature is high by using an aerator as water circulation to stabilize the water temperature of the catfish pond and provide buzzer sound notifications and Blynk notifications. if the pool water temperature is low and does not match the desired range. Research methods include hardware and software design, as well as sensor testing and system testing. The results of research on an IoT-based system are able to control the water temperature of the catfish pond so that it is at a normal temperature and monitor the temperature of the pond water which is displayed on the Blynk platform which is connected directly to the internet. The Bgt-D718-Ph temperature sensor functions well with average reading errors of 1.71% and 1.74%. In this test, research was carried out for 14 days by comparing temperature sensors and thermometer measuring instruments by taking morning and afternoon data. The temperature that occurred during the research was 2 conditions, namely high temperature and low temperature. It was found that there was a decrease in temperature during the day due to the lowest rainy weather on day 4 where the temperature reached 24.6 ℃. Then there was an increase in temperature on the 7th day reaching 35.1℃, which means the pool temperature was exposed to hot sunlight. The average sensor error value was found to be 1.41% in the morning and 1.44% in the afternoon.